CORRELATION BETWEEN APOPROTEIN B/APOPROTEIN A-I RATIO WITH HOMA IR VALUE (HOMEOSTATIC MODEL ASSESMENT INSULIN RESISTANCE) IN TYPE 2 DIABETES MELLITUS - Afandi, Muhammad Rafli; Marpaung, Ferdy Royland (Faculty of Vocational Studies, Universitas Airlangga, 2019)
Background: Diabetes mellitus (DM) is the seventh leading cause of death in the world (the occuring rate has reached 400 million people). Type2 DM is caused by the body cells' inability to respond normally to insulin (insulin resistance). Homeostatic Model Assessment-Insuline Resistance (HOMA-IR) is a calculation method which function is to measure the body insulin resistance. Diabetes mellitus can cause lipid metabolism disorders (dyslipidemia) resulting in an increased level of LDL cholesterol and decreased HDL cholesterol. The apoprotein B/apoprotein A-I ratio is the result of comparisons of apoprotein B (LDL protein constituent) and apoprotein A-I (HDL protein constituent). The apo B/apo A-I ratio represents a balance between LDL cholesterol (atherogenic) and HDL (anti-atherogenic). It is astrong signifier in predicting heart disease. Purpose: This study aim to determine the correlation between the apoprotein B/apoprotein A-I ratio with HOMA-IR in patients with type 2 diabetes mellitus. Method: Observasional, consecutive, 100 people with type 2 diabetes mellitus who is examined in apoprotein B, apoprotein A-I test that calculating the ratio in which ratio are calculated, as well as HOMA-IR in Parahita Clinical Laboratory Surabaya. This study uses Pearson correlation test method with SPSS 22.0 for Windows program. Result: The result of Pearson correlation test between apoprotein B/apoprotein A-I ratio with HOMA-IR in 100 samples is a strong and significant correlation value (r=0,610, p<0,05). Conclusion: There is a strong correlation between the apoprotein B/apoprotein A-I ratio with HOMA-IR in patients with type 2 diabetes mellitus.